Prevalence of Second-hand and Third-hand Smoke Exposure among the Medical and Dental Students - Dilruba Rahman; Tamanna Zahur; Tazdik G Chowdhury; Qazi Tanzin Ahmed; Rehana Parvin (Update Dental College, 2024)
Aim: The main objective is to estimate the prevalence of second-hand smoke (SHS) and third-hand smoke (THS) exposure among the medical and dental students of selected institutes in Bangladesh. Methods: It was a cross-sectional study conducted in March-November, 2014. A total of 501 students were selected by systematic sampling method from two medical colleges [(one govt. and one private)-Dhaka Medical College & East-West Medical College] and two dental [(one govt. and one private)-Dhaka Dental College & Update Dental College] colleges in Dhaka city, Bangladesh. Data were collected using pretested semi-structured questionnaire by face to face interview. First year to final year medical and dental students of mentioned institutes were the population of this study. Results: Among the respondents 52.3% were male and 47.7% were female. About 86% respondents were nonsmoker. From this study it was found that among the nonsmoker respondents almost all (94.4%) respondents were exposed to SHS. Indoor places were most common site followed by outdoor places for SHS exposure. More than two-third (70.5%) respondents were exposed to THS. Prevalence of THS exposure was more common at institute and home. Prevalence of SHS and THS exposure was significantly associated with gender of the respondents. Conclusion: The study revealed that, prevalence of students exposed to SHS and THS exposure were very high. Efforts should be made to plan strategy to promote smoke-free policies to protect non-smokers from SHS and THS exposure Update Dent. Coll. j: 2024; 14(1):15-18